Antimicrobial activity of a new synthetic peptide loaded in polylactic acid or poly(lactic-co-glycolic) acid nanoparticles against Pseudomonas aeruginosa, Escherichia coli O157:H7 and methicillin resistant Staphylococcus aureus (MRSA). (7th March 2017) - Cruz, J; Flórez, J; Torres, R; Urquiza, M; Gutiérrez, J A; Guzmán, F; Ortiz, C C
Abstract: Nanocarrier systems are currently being developed for peptide, protein and gene delivery to protect them in the blood circulation and in the gastrointestinal tract. Polylactic acid (PLA) and poly(lactic-co-glycolic) acid (PLGA) nanoparticles loaded with a new antimicrobial GIBIM-P5S9K peptide were obtained by the double emulsion solvent extraction/evaporation method. PLA- and PLGA-NPs were spherical with sizes between 300 and 400 nm for PLA and 200 and 300 nm for PLGA and <0.3 polydispersity index as determined by dynamic light scattering and scanning electron microscopy), having the zeta potential of >20 mV. The peptide-loading efficiency of PLA-NP and PLGA-NPs was 75% and 55%, respectively. PLA- and PLGA-NPs released around 50% of this peptide over 8 h. In 10% human sera the size of peptide loaded PLA- and PLGA-NPs increased between 25.2% and 39.3%, the PDI changed from 3.2 to 5.1 and the surface charge from −7.15 to 14.6 mV. Both peptide loaded PLA- and PLGA-NPs at 0.5 μ M peptide concentration inhibited the growth of Escherichia coli O157:H7 ( E . coli O157:H7 ), methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas. aeruginosa (P. aeruginosa) . In contrast, free peptide inhibited at 10 μ M but did not inhibit at 0.5 and 1 μ M. These PLA- and PLGA-NPs presented <10% hemolysis indicating that they are hemocompatible and promising for delivery and protection system of GIBIM-P5S9K peptide.